A longitudinal study of parental discipline up to 5 years. Issue 4 (2nd October 2021) - Lawrence, Julie; Haszard, Jillian J.; Taylor, Barry; Galland, Barbara; Gray, Andrew; Sayers, Rachel; Hanna, Maha; Taylor, Rachael
ABSTRACT: This study focuses on parental discipline techniques up to 5 years and how these change over time. A cohort of 723 mothers and fathers indicated the frequency with which they used 14 different discipline strategies during the previous week when their child was aged 6, 12, 18, 24, 42 and 60 months of age. Associations between the use of these strategies and a range of demographic, family and child factors (including depression, family quality of life, level of household chaos, parenting style and child temperament) were investigated. The range and frequency of strategies used increased with the child's age. The largest increase in the frequency of use was apparent between 6 and 12 months of age in terms of positive strategies and between 12 and 18 months for the use of negative strategies. Mothers used significantly more positive strategies during the first 24 months, and significantly more negative strategies at 18 and 24 months than fathers. Time out was popular but often poorly implemented. Greater material well-being and satisfaction with family interaction was associated with less negative discipline, and greater household chaos with more negative discipline. The level of stress, anxiety and depression reported at 24 months had little impact on later discipline.